INFLUENCE OF PARTICIPATION IN DECISION MAKING ON JOB SATISFACTION, GROUP LEARNING, AND GROUP COMMITMENT: EMPIRICAL STUDY OF PUBLIC SECTOR UNDERTAKINGS IN INDIA - Shilpi Saha; S. Pavan Kumar (Asian Academy of Management Journal, 2017)
This study assesses the impact of participation in decision making on job satisfaction, group commitment, and group learning. Data were collected from 397 managerial employees working in public sector undertakings across India. Structural equation modeling as a statistical technique and WarpPLS as a statistical tool was used to verify the proposed relationships. The findings of the study suggest that participation in decision making had a positive and significant relationship with job satisfaction. Further, participation in decision making had significant impact on group learning, but had no impact on group commitment. Job satisfaction had a positive and significant impact on group commitment. Group learning was positively and significantly related to job satisfaction and group commitment. The results suggest that employee participation in decision making process is highly desirable as it elevates employee identification with their respective organisation. The findings of the study are relevant to the people holding key managerial positions in public sector undertakings and they are discussed in detail.